Clinical course, biomarkers, management and outcomes of patients hospitalised due to COVID-19 in Colombia - Nancy Yomayusa-Gonzalez (Asociación Colombiana de Infectología, 2021)
Objective: To analyse the clinic characteristics, risk factors and evolution of the first cohort of hospitalised patients with confirmed infection by COVID-19 in 5 Colombian institutions. Materials and methods: Is a retrospective observational study of consecutive hospitalized patients with a diagnosis of COVID-19 confirmed from March 01 to May 30, 2020 in Colombia. Results: A total of 44 patients were included. The median age was 62 years. 43.2% had a history of smoking, while 69.8% were overweight or obese. 88.6% had at least one comorbidity and 52.3% had three or more comorbidities. Hypertension and dyslipidaemia were the most frequent comorbidities (40.9% and 34.1%, respectively). The 30-day mortality rate was 47.7% with a median of 11 days. The composite outcome occurred in the 36.4%. The biomarkers associated with mor-tality risk included troponin higher than 14 ng/L (RR: 5.25; 95% CI 1.37-20.1, p = 0.004) and D-dimer higher than 1000 ng/ml (RR: 3.0; 95% CI 1.4-6.3, p = 0.008). Conclusions: The clinical course of SARS-CoV-2 infection in hospitalized Colombian was characterised by a more advanced stage of the infection.